Pengaruh Optimalisasi Pelayanan dan Motivasi Kerja Terhadap Disiplin Karyawan dalam Mengukur Kepuasan Kinerja pada Tenaga Pendidikan di UPT Dinas Pendidikan Kabupaten Kutai Timur - H. Sjamsir; Amir Amir (Jurnal Administrasi Pendidikan Indonesia, 2022)
This study aimed to determine the effect of Service Optimization, Work Motivation, and Employee Discipline in Measuring Performance Satisfaction Against Education Personnel in UPT and the Department of Education in the District of East Kutai. This causal study was carried out in eighteen districts and twenty UPTs and one education department in the District of East Kutai. The research method used is a quantitative method with multiple regression. The sample of this study was 102 respondents from 459 populations. The results of this study concluded that there was a significant positive effect both partially and simultaneously between the variables Optimizing Services, Work Motivation and Employee Discipline in Measuring Performance Satisfaction Against Education personnel in UPT and the Education department in District of East Kutai. Based on the results of this study, the researchers concluded that the better a service, the more educational personnel feels more satisfied at work (1), The higher motivation at work, the more satisfaction will be at work (2), The more disciplined employees are in carrying out the tasks in force, the more satisfaction they will have at work (3), The more optimal the service, the stronger the work motivation, and the more obedient employees carry out work discipline, the more they will increase the satisfaction of performance together with the education staff so that the service will get better as well